CYTOLOGICAL STUDIES ON THE ANTIMETABOLITE ACTION OF 2,6-DIAMINOPURINE IN VICIA FABA ROOTS - Setterfield, George (The Rockefeller University Press, 1955)
At a concentration of 9.6 x 10(–5) M, 2,6-diaminopurine (DAP) completely inhibited cell enlargement, cell division, and DNA synthesis (determined by microphotometric measurement of Feulgen dye) in Vicia faba roots. Inhibition of cell enlargement was partially reversed by adenine, guanine, xanthine, adenosine, and desoxyadenosine. Guanine and the nucleosides gave the greatest reversal, suggesting that one point of DAP action upon cell enlargement is a disruption of nucleoside or nucleotide metabolism, possibly during pentosenucleic acid synthesis. DAP inhibited cell division by preventing onset of prophase. At the concentrations used it had no significant effect on the rate or appearance of mitoses in progress. Inhibition of entrance into prophase was not directly due to inhibition of DNA synthesis since approximately half of the inhibited nuclei had the doubled (4C) amount of DNA. Adenine competitively reversed DAP inhibition of cell division, giving an inhibition index of about 0.5. Guanine gave a slight reversal while xanthine, hypoxanthine, adenosine, and desoxyadenosine were inactive. A basic need for free adenine for the onset of mitosis was suggested by this reversal pattern. Meristems treated with DAP contained almost no nuclei with intermediate amounts of DNA, indicating that DAP prevented the onset of DNA synthesis while allowing that underway to reach completion. The inhibition of DNA synthesis was reversed by adenine, adenosine, and desoxyadenosine although synthesis appeared to proceed at a slower rate in reversals than in controls. Inhibition of DNA synthesis by DAP is probably through nucleoside or nucleotide metabolism. A small general depression of DNA content of nuclei in the reversal treatments was observed. This deviation from DNA "constancy" cannot be adequately explained at present although it may be a result of direct incorporation of DAP into DNA. The possible purine precursor, 4-amino-5-imidazolecarboxamide gave no reversal of DAP inhibition of cell elongation and cell division and only a slight possible reversal of inhibition of DNA synthesis.